Determinants of Households’ Adaptation Practices against Climate Change Impact on Off-farm Activities in Western Hill of Nepal - Dhungana, Ananta Raj; KC, Vikash Kumar; Khand, Purna Bahadur; Dhungana, Surya Mani (Nepal Journal of Mathematical Sciences, 2020)
Climate change is one of the serious concerns which have a substantial impact in all areas of human civilization. Among these areas, agriculture is the worst hit sector. This study aims to analyze the determinants of households’ adaptation practices against climate change impact on off-farm activities in western hill of Nepal. It utilizes the data collected from six village development committees from three districts (Lamjung, Tanahu and Kaski) of western hill of Nepal. Out of 245793 Households 556 households were chosen for the survey. A systematic random sampling technique was used to select the respondents. Data was collected using pre-tested structured questionnaire through face to face interview with household head or a household member having age 45 years and above with residing in that locality since last 15 years. Binary logistic regression analysis has been carried out. Household size is only the matter for determining the households' adaptation practices for shifting to non-agricultural activities which is also the matter for temporary migration to another places. Education is the determining factor for changing the food consumption habit and temporary migration. Agriculture skill is the common determining factor for change in food consumption habit and shifting to non-agricultural activities. Sex and marital status are the major determining factors only for shifting to non-agricultural employment. Age is the significant predictor of temporary migration. Caste is also the major determining factor for changing the food consumption habit and temporary migration respectively.